PEMANFAATAN KERANG FORTIFIKASI KALSIUM PADA KRUPUK ANEKA RASA UNTUK PENINGKATAN KANDUNGAN GIZI DAN TINGKAT PENERIMAAN KONSUMEN - Evawati, Diana (Jurnal AKP, 2010)
Shell is a commodity which known well by community and as kind of cheap seafood, protein-rich, containsabundant of essential amino acid (arginine, leusin and lisin). The sell has approximately 30% of flesh fromthe total weight and have many kinds of mineral calcium, phosphate, iron, iodium and copper. Due to theabundance of the protein of the shell, itâs important to optimizing the benefit of the shell and this researchconduct to perform calcium fortification on the chip to improve the nutrition value of the chip and improvethe opportunities in post production of fishery.This research was laboratory and experimental research by random complete-design which conduct by fivetreatments: T0.T1,T2,T3,T4, counted by RDA and the repetition of each treatment done in four times so thetotal amount of the test was twenty times. The calculation of the protein level was done by Micro-Kjeldalmethod. While the calculation of the calcium and organoleptic value wasvdone by Hedonic scale by expertpanelists.Result of the experiment was the color of the shell chips (10%) is higher and the increasing of as on thecalcium fortified-chips is positively correlated to the calcium level on its. The analysis of bioavailabilitydone by in vitro method,and the result was only 12.93% of calcium which is absorbed to the body and onthe control chips, while 6,09% of calcium of the 10% calcium fortified-chips absorbed to the body.